The Relationship between Health Information Technology Laboratory Tracking Systems and Hospital Financial Performance and Quality. Issue 3 (3rd July 2019) - Zhao, Mei; Hamadi, Hanadi; Rob Haley, D.; White-Williams, Cynthia; Liu, Xinliang; Spaulding, Aaron
Abstract: The objective of this study is to explore the relationship between hospitals Health Information Technology (HIT), and financial and quality performance. The study merged the 2017 Centers for Medicare & Medicaid Services (CMS) Healthcare Cost Report Information System, American Hospital Association Annual Survey, and two CMS Hospital Compare datasets. A total of 3002 hospitals were analyzed using multivariate analysis. We found that hospitals with laboratory tracking systems reported better financial performance on five financial performance measures. Policymakers should consider developing policies that facilitate exploration and adoption of various hospital HIT capabilities that measurably improves hospital quality of care.